-(-2n-5)=-13-n

Simple and best practice solution for -(-2n-5)=-13-n equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -(-2n-5)=-13-n equation:


Simplifying
-1(-2n + -5) = -13 + -1n

Reorder the terms:
-1(-5 + -2n) = -13 + -1n
(-5 * -1 + -2n * -1) = -13 + -1n
(5 + 2n) = -13 + -1n

Solving
5 + 2n = -13 + -1n

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add 'n' to each side of the equation.
5 + 2n + n = -13 + -1n + n

Combine like terms: 2n + n = 3n
5 + 3n = -13 + -1n + n

Combine like terms: -1n + n = 0
5 + 3n = -13 + 0
5 + 3n = -13

Add '-5' to each side of the equation.
5 + -5 + 3n = -13 + -5

Combine like terms: 5 + -5 = 0
0 + 3n = -13 + -5
3n = -13 + -5

Combine like terms: -13 + -5 = -18
3n = -18

Divide each side by '3'.
n = -6

Simplifying
n = -6

See similar equations:

| 2(3*-4)=22 | | x11/20*30 | | x=11/30x230 | | 4k-5=6k+1 | | 5(m-4)=2m+3 | | -2(z-11/5)=3z | | 2x^2-6x-9=89 | | 18=-8x+6x | | 7+6x+6x=47 | | 4x^2-16x-33=0 | | 5/6x-7/8=1/6x-1/4 | | 3/2x-(3-4x)=1/3 | | 3(3)+2(5)=60x-500 | | 5+14a=9x-5 | | 2/3×-11=14 | | -.12x^2+2.4x=8 | | y=7sinx-4 | | (x-1/3x)^2 | | 2x^3+6x^2=1 | | x=2(x+29) | | -54x=10 | | x=2x+58 | | 17x-6=10x-13 | | p=2x+58 | | 48*38= | | x=6+9 | | 7x-2-2x+5=-2x+1+6x | | 1.52=3.16(y-8.62) | | 1.52=(y-8.62) | | ydx=(3x-y^3)dy | | 6n+9=-3n-27 | | y=0.25(x-5)(x-1) |

Equations solver categories